HISTOPATHOLOGICAL STUDY OF LUNG CHANGES IN COVID -19 CASES: AUTOPSY STUDY (Journal of Forensic Medicine & Toxicology, 2025)
A novel coronavirus-severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) hit the world towards the end of 2019. This has caused deaths worldwide. Lungs being the primary site for COVID-19 pathology. We attempt a retrospective histopathology study of the lung changes due to SARS–CoV-2 infection of all the medicolegal autopsies done for covid patients for two years (June 2020 to May 2022). Postmortem lung samples of persons who died due to Covid 19 infection were collected in 10% formalin. A total of 71 cases were studied. Representative bits from the lungs were processed. Histopathology sections were stained with hematoxylin and eosin (H & E) stain and special stains were used as and when required. The gross and microscopic findings were studied. Of these 53 were males (74.64 %) & 18 females (25.35%). The age group of the study population ranged from 23 days to 92 years. The major histopathological findings noted were pulmonary edema, pneumonia, intrapulmonary hemorrhage, chronic phase of diffuse alveolar damage, acute phase of diffuse alveolar damage, subacute phase of diffuse alveolar damage, microthrombi, pneumonia with abscess formation. Acute pneumonia with consolidation was seen in 20 cases (28.1%), intrapulmonary hemorrhage in 15 cases (21.1%), chronic phase of diffuse alveolar damage in 9 cases (12.6%), acute phase of DAD was seen in 7 cases (9.8%), subacute phase in 6 cases (8.4%).
Keywords: COVID-19; SARS CoV–2; Medico-legal Autopsy; Lungs; Histopathology